2023
DOI: 10.3390/diagnostics13030388
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation, Cryoablation, and Microwave Ablation for the Treatment of Small Renal Masses: Efficacy and Complications

Abstract: Over the last two decades the detection rate of small renal masses has increased, due to improving diagnostic accuracy, and nephron-sparing treatments have become the first-choice curative option for small renal masses. As a minimally invasive alternative, thermal ablation has increased in popularity, offering a good clinical outcome and low recurrence rate. Radiofrequency ablation, Cryoablation, and Microwave ablation are the main ablative techniques. All of them are mostly overlapping in term of cancer speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…They stated a 5-year cancer-specific survival of about 95-98%. 8 MWA also had the benefit of shorter procedural and ablation times compared to the cryoablation and RFA groups. A systematic review and meta-analysis of comparison studies comparing efficacy and safety of MWA against RFA and cryoablation was undertaken by Castellana et al 9 The study included a total of 2258 thermal ablations and concluded that MWA is as effective and safe as RFA and cryoablation in addition to encountering fewer recurrences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They stated a 5-year cancer-specific survival of about 95-98%. 8 MWA also had the benefit of shorter procedural and ablation times compared to the cryoablation and RFA groups. A systematic review and meta-analysis of comparison studies comparing efficacy and safety of MWA against RFA and cryoablation was undertaken by Castellana et al 9 The study included a total of 2258 thermal ablations and concluded that MWA is as effective and safe as RFA and cryoablation in addition to encountering fewer recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…This was despite the MWA group having a larger median tumour size compared to cryoablation (no difference in local or metastatic recurrence). They stated a 5‐year cancer‐specific survival of about 95–98% 8 . MWA also had the benefit of shorter procedural and ablation times compared to the cryoablation and RFA groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, CA is associated with a higher risk of hemorrhage because the surrounding blood arteries are not directly cauterized, such as in RFA, where heat has an intrinsic coagulative effect and reduces the risk of minor hemorrhage. Moreover, CA usually requires the insertion of multiple probes to create an adequate ice ball, and the procedure is longer, resulting in a higher amount of tissue damage [36].…”
Section: Discussionmentioning
confidence: 99%